Nickel oxide nanoparticles are highly toxic to SH-SY5Y neuronal cells. (September 2017) - Abudayyak, Mahmoud; Guzel, Elif; Özhan, Gül
Abstract: Nickel oxide nanoparticles (NiO-NPs) are used in many industrial sectors including printing inks, ceramics and catalysts, and electrical and electronics industry because of their magnetic and optical properties. However, there has been still a serious lack of information about their toxicity at the cellular and molecular levels on nervous system. For that, we aimed to investigate the in vitro toxic potentials of NiO-NPs in neuronal (SH-SY5Y) cells. The particle characterisation, cellular uptake and morphological changes were determined using Transmission Electron Microscopy, dynamic light scattering and Inductively Coupled Plasma-Mass Spectrometry. Then, the cytotoxicity was evaluated by MTT and neutral red uptake assays, the genotoxicity by comet assay, the oxidative potentials by the determination of malondialdehyde, 8-hydroxy deoxyguanosine, protein carbonyl, and glutathione levels with Enzyme-Linked Immune Sorbent Assays, and the apoptotic potentials by Annexin V-FITC apoptosis detection assay with propidium iodide. According to the results, it was observed that NiO-NPs (15.0 nm ± 4.2–38.1 nm); (i) were taken up by the cells in concentration dependent manner, (ii) caused 50% inhibition in cell viability at ≥229.34 μg/mL, (iii) induced some morphological changes, (iv) induced dose-dependent DNA damage (3.2–11.0 fold) and apoptosis (80–99%), (v) significantly induced oxidative damage. In conclusion, our results support the hypothesis that NiO-NPs affect human health especially neuronal system negatively and should raise the concern about the safety associated with their applications in consumer products.